Construction of tissue-engineered human corneal endothelium for corneal endothelial regeneration using a crosslinked amniotic membrane scaffold. (15th July 2022) - Zhao, Jun; Tian, Meng; Li, Yun; Su, Wen; Fan, Tingjun
Abstract: Descemet's membrane endothelial keratoplasty (DMEK) may provide fast visual rehabilitation in the therapy of corneal endothelial disorders. However, due to shortage of donated corneas, how to construct a corneal endothelial substitute with powerful functions that can be used for DMEK is still unsolved. Herein, we introduced the method of corneal crosslinking (CXL) and conjugated the components of native Descemet's membrane (DM) to improve the mechanical properties and the biocompatibility of denuded amniotic membrane (dAM), further assessed their effects on cell adhesion, proliferation, YAP translocation, and metabolic activity in human corneal endothelial (HCE) cells. Using modified crosslinked dAM (mcdAM) and non-transfected HCE cells, we constructed a tissue-engineered HCE (TE-HCE) and evaluated its functions in cat and monkey models as well. Our results showed that the mechanical properties of mcdAM were improved effectively by CXL, and the adhesion, proliferation, and YAP translocation of HCE cells were dose-dependently improved after ECM modification. The combination of 0.01 mg/mL laminin with 0.1 mg/mL fibronectin showed the highest efficacy. Then, the TE-HCE was constructed in vitro, with a high density of 3612 ± 243 cells/mm 2 . Results of DMEK in animal models showed that corneal transparency was maintained, accompanied with normal morphology and histological structure of the regenerated corneal endothelium. Therefore, CXL combined with DM-mimic-coating methods could effectively improve the mechanical properties of dAM and enhance the biocompatibility with HCE cells. The constructed TE-HCE had normal histological structure and functioned well in animal models via DMEK, which could be used as a promising powerful equivalent of HCE. Statement of significance: Using high-quality corneal endothelium and an appropriate endothelial keratoplasty is the most effective way for the treatment of corneal endotheliopathy. Descemet's membrane endothelial keratoplasty (DMEK) which can provide better visual acuity, lower immunological rejection rates, and improved graft survival is an ideal surgery at present. However, due to the shortage of donated corneas, it is urgent to find an equivalent substitute of corneal endothelial donor which is suitable for the DMEK surgery to solve the problem of corneal endothelial regeneration. Herein, we introduced the clinical cornea-crosslinking and Descemet's membrane-mimic-coating methods to build the modified crosslinked denuded amniotic membrane scaffold and further constructed a high-quality corneal endothelial functional substitute that can be used in DMEK surgery. Graphical abstract: Image, graphical abstract